2022
DOI: 10.1002/cmdc.202200026
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold Hopping from Amodiaquine to Novel Nurr1 Agonist Chemotypes via Microscale Analogue Libraries

Abstract: Several lines of evidence suggest the ligand-sensing transcription factor Nurr1 as a promising target to treat neurodegenerative diseases. Nurr1 modulators to validate and exploit this therapeutic potential are rare, however. To identify novel Nurr1 agonist chemotypes, we have employed the Nurr1 activator amodiaquine as template for microscale analogue library synthesis. The first set of analogues was based on the 7chloroquiolin-4-amine core fragment of amodiaquine and revealed superior N-substituents compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Interestingly, statins share structural features with known Nurr1 modulators. Fluvastatin and pitavastatin comprise a similar bicyclic nitrogen‐containing scaffold as AQ, [ 3 ] CQ [ 3 ] (Figure 1c ), and analogues [ 15 , 23 ] which is also contained in the Nurr1 binding dopamine metabolite dihydroxyindole [ 13 , 24 ] and indole‐based Nurr1 modulators. [ 25 ] Atorvastatin and rosuvastatin share substructures with certain non‐steroidal anti‐inflammatory drugs (NSAIDs), which were found to bind Nurr1, too.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, statins share structural features with known Nurr1 modulators. Fluvastatin and pitavastatin comprise a similar bicyclic nitrogen‐containing scaffold as AQ, [ 3 ] CQ [ 3 ] (Figure 1c ), and analogues [ 15 , 23 ] which is also contained in the Nurr1 binding dopamine metabolite dihydroxyindole [ 13 , 24 ] and indole‐based Nurr1 modulators. [ 25 ] Atorvastatin and rosuvastatin share substructures with certain non‐steroidal anti‐inflammatory drugs (NSAIDs), which were found to bind Nurr1, too.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear receptor related 1 (Nurr1, NR4A2) is a constitutively active ligand-activated transcription factor predominantly expressed in neurons. It has neuroprotective and antineuroinflammatory activity and emerges as an attractive target to treat neurodegenerative pathologies including Alzheimer’s disease (AD), Parkinson’s disease (PD), and multiple sclerosis (MS). , Therapeutic potential of Nurr1 activation is supported by observations from several rodent models, demonstrating that Nurr1 knockout produces a PD-like phenotype and that diminished Nurr1 activity aggravates disease models of AD, PD, and MS. Moreover, human patients of these pathologies were found to exhibit diminished Nurr1 expression, and the neuroprotective effects of statin drugs could in part be referred to Nurr1 activation, further highlighting the receptor’s promise. However, validation of pharmacological Nurr1 activation as an approach to treat neurodegenerative diseases is pending, since selective chemical tools with high Nurr1 agonist potency are lacking. , Although the anticipated therapeutic potential of Nurr1 as a neuroprotector has fueled efforts to develop Nurr1 agonists , and inverse agonists, , the micromolar potency of available Nurr1 modulators is insufficient . Here, we report the first Nurr1 agonist scaffold achieving nanomolar potency.…”
Section: Introductionmentioning
confidence: 95%
“…75,[114][115][116] Our structure activity relationship studies on chloroquinolineamines derived from 11 have revealed the potential to generate improved Nurr1 agonists from this scaffold and provided insights into Nurr1 activation mechanisms. 117,118 For a number of other putative Nurr1 ligands, systematic NMR-based binding studies have raised concerns about direct interaction. 119 These findings also compromise the observations of studies on Nurr1 biology using the compounds in question and highlight the importance of extensive characterization of tools for target identification and validation experiments.…”
Section: Chemical Tool Development For Orphan Nrsmentioning
confidence: 99%